Approximate Solution of Fourth Order Near Critically Damped Nonlinear Systems with Special Conditions (Journal of Bangladesh Academy of Sciences, 2012)
A perturbation technique has been developed based on the Krylov-Bogoliubov-Mitropolskii (KBM) method to investigate the solution of fourth order near critically damped nonlinear systems in the case of ?1??2, ?4 ? ?3 + 2?1 but ?4